The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1007/bf03347856
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between follicle stimulating hormone and the growth hormone - insulin-like growth factor - IGF-binding proteins axes in human granulosa cells in culture

Abstract: As it has been hypothesized that IGF-binding proteins (IGFBPs) may have a role as autocrine/paracrine factors in regulating the local actions of the insulin-like growth factors (IGFs) in the ovary, we studied the production of the IGFBPs by human granulosa cells (GC) in culture and the role of IGFBP-3 in the modulation of ovarian cell responsiveness to IGF-I and FSH. To this purpose, human luteinizing GC were cultured in serum-free conditions for 24 h and subsequently submitted to increasing concentrations (2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In this cancer cell line, membrane-bound IGFBP-3 inhibited growth induced by IGF-I and not by des-(1-3)-IGF-I [101]. Similar sequestration effects have been demonstrated in human osteoarthritic chondrocytes [102]and human granulosa cells [103]. A comparison of serum levels of IGF-I and IGF-II versus IGFBP-2 through -5 in bovine first-wave dominant follicles showed that the IGF-I/IGFBP ratio decreased with atresia of the follicles [104].…”
Section: Igf-dependent Actions Of Igfbpsmentioning
confidence: 51%
“…In this cancer cell line, membrane-bound IGFBP-3 inhibited growth induced by IGF-I and not by des-(1-3)-IGF-I [101]. Similar sequestration effects have been demonstrated in human osteoarthritic chondrocytes [102]and human granulosa cells [103]. A comparison of serum levels of IGF-I and IGF-II versus IGFBP-2 through -5 in bovine first-wave dominant follicles showed that the IGF-I/IGFBP ratio decreased with atresia of the follicles [104].…”
Section: Igf-dependent Actions Of Igfbpsmentioning
confidence: 51%
“…IGFBP-3, for example, can directly bind to cellular targets involved in the cell-cycle, including the ribonucleic acid polymerase II binding subunit 3 (Rpb3), suggesting a possible role of IGFBP-3 in directly regulating gene transcription [43]. The effects of IGFBP-3 on cell-cycle are largely opposite to those of IGF-I since IGFBP-3 is pro-apoptotic [4453] and anti-proliferative [52,5458]. Although the IGFBP family was recently expanded to include nine IGFBP-rPs that can bind IGF-I and IGF-II [3,59], some investigators have challenged their inclusion due to absence of clear phylogenetic relationships between the IGFBP-rPs and the IGFBPs [60], and the limited understanding of IGFBP-rP function.…”
Section: Overview Of the Igf-axismentioning
confidence: 99%
“…IGFBPs clearly modulate the interactions between IGFs and Type I IGF receptors on the cell surface ( [102] and human granulosa cells [103]. A comparison of serum levels of IGF-I and IGF-II versus IGFBP-2 through -5 in bovine first-wave dominant follicles showed that the IGF-I/IGFBP ratio decreased with atresia of the follicles [104].…”
Section: Igf-dependent Actions Of Igfbpsmentioning
confidence: 99%